Answer:
y = -2x + 7
Step-by-step explanation:
The equation of a line could be represented as original form:
y = ax + b
Let's pick the first 2 pairs of numbers in the table: (x, y) = (1, 5) and (x, y) = (2, 3).
=> 5 = a*1 + b
3 = a*2 + b
Subtract the 1st equation from the 2nd equation, we have:
-2 = (2a - a) + (b - b)
or
-2 = a
Substitute a = -2 into the 1st equation, we have:
5 = (-2)*1 + b
or
5 = -2 + b
or
b = 2 + 5 = 7
=> Substitute a = -2 and b = 7 into original form, the equation that represents the data shown in the table is:
y = -2x + 7
Hope this helps!